가계대출상품 선택과 연체율 결정요인에 대한 실증분석 - 류주연(Juyoun Ryoo); 전진규(Jin Q Jeon) (대한경영학회지, 2017)
세계 금융위기의 주요 원인 중 하나로 가계발 대출 부실화를 들 수 있다. 우리나라의 경우 지난 20년 동안국민소득 증가에도 불구하고 주택가격 상승 및 생계비 증가 등으로 인하여 2015년 말 기준 전체 가계신용잔액은 1,352.9조원, 주택담보대출 잔액 608.8조원으로 사상 최고치를 기록하였다. 가계부채의 원리금상환부담은 가계의 소비 여력을 위축시키고, 시중금리 상승 시 가계부채의 부실화 가능성이 높아져 이에 대한처리문제가 사회적으로 이슈화가 되고 있다. 이에 정부는 주택금융시장의 건전성 확보 및 리스크 분산을 위하여장기 고정금리 및 원리금분할 방식 대출을 정책적으로 장려하고 있다. 본 연구에서는 고정금리·원리금분할상환 대출이 정책적으로 장려되고 있는 상황에서 주택담보대출의 금리유형 및 상환구조 선택의 결정요인 분석하였다. 국내 시중은행들로부터 2010년부터 2014년까지 발생한5,636,802건의 주택담보대출을 대상으로 대출 상품 결정요인을 분석한 결과 차주의 연소득 변동성(Income Risk)의 주요 변수인 연소득, 나이, 신용등급 등에 따라 고정·변동금리 대출의 선호가 달라지는 것으로나타났으며, 주택가격 상승률이 높을 경우 변동금리의 선호현상이 강화되는 결과를 보였다. 또한 장단기금리차가 커질 경우 단기 금리인 변동금리와 장기금리인 고정금리 간의 격차 역시 증가하여 고정금리 대출선호현상이 감소하는 것으로 나타났다. 주택담보대출 연체율 결정요인을 분석한 결과 전체 연구기간에서 고정금리 및 원리금 분할상환 대출은연체율을 유의적으로 높이는 것으로 나타났다. 금리가 상승했던 2005년부터 2008년에 발생한 대출만을 별도로분석한 결과 변동금리대출과 고정금리대출의 연체율은 유의적 차이가 없었으며, 분할상환 대출은 상대적으로연체율이 높은 것으로 나타났다. 본 연구의 결과가 금융당국의 주택금융 정책에 시사하는 바는 은행의 효율적장기자금 조달을 통해 고정·변동금리의 격차를 낮출 필요가 있는 점이다. 또한 연소득이 낮은 차주를 고정금리대출로 전환 유도 시 안심전환대출과 같은 저소득자 지원방안이 필요하며, 분할상환에 따른 원리금상환 부담을낮추기 위하여 금리 및 만기를 조정할 필요가 있다 One of the key sources of global financial crisis is households debt insolvency. In Korea, the total households debt reached to 1,352.9 billion wons and housing loan reached to 608.8 billion wons at the end of year 2015. Economists see little risk of the debt prompting a financial crisis, nothing Korea’s moderate loan-to-value rations and historically low default rates. Nevertheless, in order to push borrowers towards more manageable and predictable repayment schedules, the Korean government set the target proportion of fixed-rate and amortising home loans: fixed-rate and amortising home loans must each account for 40 percent of banks' residential mortgage holdings by 2017. In the circumstance that fixed and installment housing loans are encouraged by the government, this paper examines the determinants of the choice between fixed and adjustable rates and between bullet and installment housing loans. We use the broad data of home loans up to 5,636,802 loans occurred from 2010 to 2014. These data are collected from all the Korean commercial banks. Among the sample loans, 3,886,214 loans employ adjustable rates and 955,113 loans employ fixed rates, while the other 789,251 are the loans with mixed rates. 1,899,563 loans use bullet payments, 1,964,052 loans use installment payment with terms unredeemed, although 1,538,295 are installment payment loans without terms unredeemed. By applying various empirical methods, we find that the income risk factors such as annual income, age and credit scores are the key determinants, while the other factors such as wealth risk and policy risk are important, too. For example, an increase in housing price lead higher preference to fixed rate loans, which is the evidence that wealth risk is an improtant factor. Also, adjustable-rate loans are preferred when the housing price increases and when the term structure spread is larger. We also investigate the determinants of the overdue rate of housing loans and find that, during the whole sample period, the overdue rate of fixed-rate and amortising loans is larger than that of adjustable-rate and bullet loans. The main reason of this findings is that loan holders are more concerned with higher fixed rate and feel burden to installment payment. However, during the year 2005 and 2008, when the interest rate increased, we do not find any difference in the default rate between fixed-rate and adjustable-rate loans, while amortising loans still have the higher overdue rate. This study is the first to analyze the large dataset of housing loans provided by commercial banks. Our results provide important suggestions regarding the government policy on housing loans. First, the key determinant on the choice of housing loans is the spread between fixed rates and adjustable rates. This suggests that if the government want to increase the use of fixed rate loans, they need to set the policy to decrease the spread. In the banks’ perspective, in order to decrease the spread, banks need to finance long-term funds more efficiently. For example, they may use long-term debts such as the MBS or covered bonds. Second, according to our findings, people with lower income are more likely to use adjusted rate and bullet payment loans. In that they have the more possibility to be exposed to be default with an increase in interest rates, the government need to set various policy to support those lower income lenders by enhancing welfare policy on financing as well as employment. In addition, higher installment payment is positively correlated with house defaults. In order to reduce installment payments, it is important to set the loan maturity efficiently. Note that if the maturity is too short lenders need pay more installment, while if it is too long lenders more likely to be exposed to interest rate risk. KCI Citation Count: 3